2014
DOI: 10.2466/25.29.pms.119c30z3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Set Configuration of Resistance Exercise on Perceived Exertion

Abstract: Set configuration refers to the repetitions performed with regard to the maximum possible number of repetitions, a factor affecting RPE that has not been previously studied. This study analyzed the effect of set configuration and muscle mass on RPE. Eight students (M age = 23.7 yr. ± 1.7) completed four sessions corresponding to types of exercise with different amount of muscle mass (bench press and parallel squat) and two set configurations: a session with five sets of repetitions to failure and a cluster ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 31 publications
5
35
3
2
Order By: Relevance
“…However, a previous study has shown that the lower BP response during ISR in comparison with TS remained even when the work-to-rest ratios are equated for both configurations [ 8 ], suggesting that other factors underlie these differences. We proposed that ISR induces lower levels of muscle fatigue, compared with TS, since this configuration is associated with improved mechanical performance [ 9 ] and less perceived effort [ 4 , 8 , 10 ]. Moreover, peripheral and central fatigue may play differential roles in each configuration.…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study has shown that the lower BP response during ISR in comparison with TS remained even when the work-to-rest ratios are equated for both configurations [ 8 ], suggesting that other factors underlie these differences. We proposed that ISR induces lower levels of muscle fatigue, compared with TS, since this configuration is associated with improved mechanical performance [ 9 ] and less perceived effort [ 4 , 8 , 10 ]. Moreover, peripheral and central fatigue may play differential roles in each configuration.…”
Section: Introductionmentioning
confidence: 99%
“…RPE increased in successive sets of all exercises. This finding shows RPE increases in successive sets even without increasing the load, perhaps because of the cumulative energy expenditure caused by successive sets (Mayo, Iglesias-Soler, & Del-Olmo, 2014) or increased anabolic metabolites (Robertson et al, 2003).…”
Section: )mentioning
confidence: 81%
“…The adaptations to resistance training can be modulated by manipulating some variables such as volume, frequency, velocity, load, work-to-rest ratio or set configuration. This study is focused on the set configuration which is defined by the repetitions performed in a set with regard to the maximum feasible number of repetitions (Iglesias-Soler et al, 2016;Mayo, Iglesias-Soler, & Fernández-Del-Olmo, 2014). In this sense, manipulating the number of repetitions contained in a set has been proven to be an effective way for inducing different types of neural and muscular adaptations (Iglesias-Soler et al, 2017;Morales-Artacho, Padial, García-Ramos, Pérez-Castilla, & Feriche, 2018;.…”
Section: Introductionmentioning
confidence: 99%